2014
DOI: 10.1128/iai.00864-13
|View full text |Cite
|
Sign up to set email alerts
|

Internalization and Trafficking of Nontypeable Haemophilus influenzae in Human Respiratory Epithelial Cells and Roles of IgA1 Proteases for Optimal Invasion and Persistence

Abstract: Nontypeable Haemophilus influenzae (NTHI) is a leading cause of opportunistic infections of the respiratory tract in children and adults. Although considered an extracellular pathogen, NTHI has been observed repeatedly within and between cells of the human respiratory tract, and these observations have been correlated to symptomatic infection. These findings are intriguing in light of the knowledge that NTHI persists in the respiratory tract despite antibiotic therapy and the development of bactericidal antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(80 citation statements)
references
References 54 publications
4
76
0
Order By: Relevance
“…5). These data suggest that Arp2/3 participates in NTHI internalization with subsequent intracellular trafficking to the endolysosomal pathway (59).…”
Section: Fig 2 Graphical Summary Of Overrepresented Proteins Categomentioning
confidence: 87%
“…5). These data suggest that Arp2/3 participates in NTHI internalization with subsequent intracellular trafficking to the endolysosomal pathway (59).…”
Section: Fig 2 Graphical Summary Of Overrepresented Proteins Categomentioning
confidence: 87%
“…Interestingly, AO and monodansylcadaverine staining have revealed the nature of acidic vacuolar compartments containing large numbers of NTHi to be derived from autophagosomes. Recent studies have suggested the role of lysosomal machinery (lysotracker, lamp-1, lamp-2, CD63, and Rab7) (Morey et al, 2011;Clementi et al, 2014) but no autophagic markers had been linked with NTHi vacuolar uptake. Future studies are required to broadly monitor the role of autophagy during NTHi infection using more rigorous markers.…”
Section: Discussionmentioning
confidence: 98%
“…We were able to enumerate the viable number of intracellular NTHi until 8 h as monolayer begins to lose its integrity at later time points of infection. Recently, Clementi et al (2014) reported killing of intracellular NTHi in lysosomes 24 h postinfection. Differences observed in terms of time points of infection between our data and previous reports could be due to variation in experimental conditions, procedures, host cell types, NTHi strains, and MOI used.…”
Section: Discussionmentioning
confidence: 99%
“…S1 in the supplemental material). We and others previously described that NTHI invades epithelial cells and localizes to an NTHI-containing vacuole (NTHI-CV), a nonproliferative compartment with late endosome features (51,57,58). Given that macrolides present good penetration of lung tissue, are acid resistant, and accumulate in lysosome-like compartments (11), we asked if AZM could modulate NTHI in- .…”
Section: Selection Of Two Nthi Clinical Isolates With Different Suscementioning
confidence: 99%